THE COMPARISON OF THE STORAGE TEMPERATURE ON DIAMETRAL TENSILE STRENGHT VALUE OF BULK-FILL RESIN COMPOSITE - Niketa Khairina; Dewi Puspitasari; Sherli Diana (Dentino : Jurnal Kedokteran Gigi, 2018)
Background: The decrease and increase of bulk-fill composite resin storage temperature are infunction to extend the expiration period and obtain lower viscosity, making it easier for application of composite resin. Temperature is one that affects the polymerization process. Different polymerization qualities will affect the physical and mechanical properties of the composite resin, one of which is the diametral tensile strength. Purpose: To analyze the difference of tensile strength value of diametral bulk-fill composite resin stored at low temperature (5˚C), room temperature (25˚C) and high temperature (35˚C). Method: 33 specimens with 6 mm diameterand 3 mm thicknesswere divided into three treatment groups consisted oflow temperature storage group (5˚C), room temperature group (25˚C)and high temperature group (35˚C). The diametral tensile strength wasmeasured by Universal Testing Machine and analyzed by One Way Anova and Post Bonfond Bonferroni test. Result: The mean diametral tensile strength of bulk-fill composite resin with storage temperature 5˚C (35,85 MPa), 25˚C (42,72 MPa) and 35˚C (45,73 MPa). One Way Anova Test obtained p value = 0,001 (p>0,05) and continued with Post Hoc Bonferroni, so it can be concludedthat there was significant difference in the value of diametral tensile strength of bulk-fill composite resin with 25˚C and 35˚C storage temperature compared with 5˚C, and there was no significant difference in diametraltensile strengthof bulk-fill composite resin by comparing the temperature treatment of 25˚C with 35˚C. Conclusion: The diametral tensile strength value of the bulk-fill composite resin are increased as the storage temperature increase.